The Use of Medicinal Leeches in Plastic Surgery - Kosta Y. Mumcuoglu; Aysegül Taylan-Özkan (Turkish Journal of Plastic Surgery)
Leech therapy, or hirudotherapy (HT), has been utilized in medicine for centuries, with applications ranging from bloodletting to modern reconstructive and plastic surgery. This paper explores the historical evolution of leech use in plastic surgery, the types of medical leeches employed, and their mechanisms of action. Although surgery is the standard approach to treating venous stasis, microvascular surgeons can use medical leeches to treat resistant cases. It is an easy-to-use, useful, and cost-effective treatment method practiced in most countries, especially in plastic surgery departments, for saving replanted limbs and grafts. It plays a crucial role in managing venous congestion following replantation and flap surgeries, helping to restore microcirculatory balance and angiogenesis. The mechanisms include anticoagulation, vasodilation, and bloodletting, which are facilitated by the bioactive compounds in leech saliva. The process of HT in plastic surgery involves pretreatment preparations, precise application of the leeches, monitoring of treatment, and assessment of potential contraindications and side effects. Prophylactic treatment with antibiotics and continuous monitoring of blood parameters are also important throughout treatment. In this review, the appropriate maintenance of leeches in clinical settings, as well as the situation in Türkiye, will be briefly discussed.